Nepal : Electronic Government Procurement Readiness Assessment and Roadmap - World Bank (World Bank, Washington, DC, 2013)
The assessment focused on the degree of readiness of Government of Nepal's (GoN's) current public procurement environment for making a transition from a traditional paper-based, manual procurement transaction processing and communication to electronic government procurement (e-GP). Some 20 public and private sector organizations, involved in a wide range of functions that relate to public procurement, provided comment on the degree of readiness of nine key components related to e-GP: leadership, human resource planning, procurement planning and management, procurement policy, legislation and regulation, Internet and electronic infrastructure, standards, private sector integration, and current e-GP systems and initiatives. The assessment found: adequate evidence that an e-Tendering system is in place but is little used; some evidence that procurement legislation and procurement planning is in place and being supported, and that some procurement training has been conducted; and limited evidence that leadership, human resource planning, procurement management, regulation, and Internet infrastructure services are in place and being supported. The Roadmap sets out the features for a comprehensive e-GP service including e-Tendering, e-Purchasing, e-Reverse Auctioning, and a Procurement Information and Management System.